The Dichotomy of Juz’i and Kulli in the Subject of Islamic Theology: A Preliminary Proposal - Sogukoglu, Fehmi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This article examines the inclusion of kulli (universal) and juz’i (particular) aspects in kalam (Islamic theology). Many theologians after al-Ghazali have emphasized the universality of kalam within the Islamic sciences. Kalam aims to offer rational justifications for the existence and unity of Allah SWT, the mission of the Prophet (PBUH), and the divine origin of the Qur’an. Other fields in Islamic studies require evidence from kalam to support their arguments, while kalam is considered a kulli source of legitimacy. However, some kalam issues derive solely from textual sources, similar to other Islamic sciences. This article presents these topics as a juz’i aspect of kalam. Studying past and present theologians' practices exposes methodological distinctions between kulli and juz’i issues. Given that ahad sources is utilized in specific subjects, it can be posited that the mutakallimun’s comprehension of ‘knowledge’ pertains to the kulli subjects of kalam. This differentiation may also contribute to distinguishing between kalam and ‘aqa’id.